Grain size effects in BaTi0.90Hf0.10O3 ceramics with phase coexistence: the influence of nanostructuring and of the internal stress on the functional properties - Soare, Elena Mirabela; Stanciu, Cătălina Andreea; Pătru, Roxana Elena; Surdu, Vasile Adrian; Pădurariu, Leontin; Horchidan, Nadejda; Nicoară, Adrian Ionuț; Trupină, Lucian; Vasile, Bogdan Ștefan; Trușcă, Roxana Doina; Mitoșeriu, Liliana; Ianculescu, Adelina Carmen (Elsevier B.V., 2025)
The present study is focused on describing the influence of the sintering method (fast field-assisted Spark Plasma Sintering vs. conventional sintering) on the functional properties of BaTi0.90Hf0.10O3 ceramics with polymorph superposition around room temperature. Dense ceramics, derived from nanopowders synthesized via Pechini method, with grain size downscaled from 3.7 to 0.07 μm were prepared using different sintering strategies. XRD data at room temperature revealed the presence of mixtures of dissimilar structural modifications either for the starting nanopowder, as well as for the related ceramics. The Landau-based calculations indicated that different amounts of polymorphs are stable in these ceramics, by considering the grain size reduction and the strain-stress fields produced by the fast sintering method, thus confirming the experimental results of the structural and Raman analyses. By decreasing the average grain size from micro-to nanoscale, a slight decrease of the Curie temperature, accompanied by the increase of the diffuseness of the ferroelectric-to-paraelectric phase transition and the decrease of both the permittivity maxima and the dielectric losses was detected. Both the dielectric response and the ferroelectric P(E) loops indicated a ferroelectric-relaxor crossover as the grain size decreased in the nanometre range. The beneficial effect of the nanostructuring on the energy storage efficiency was also revealed.
Keywords: BaTi0.90Hf0.10O3 ceramics; Landau-based calculations; Phase superposition; Spark plasma sintering; Energy storage properties